Implementasi Arduino Iot Cloud: Potensiometer Sebagai Pengatur Intensitas Cahaya LED - Iis Setiawan Mangkunegara; Arif Setia Sandi Ariyanto; Deny Nugroho Triwibowo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Development of the Internet of Things in this modern technological era plays a significant role in aiding and simplifying tasks across various industrial sectors. One of the open-source electronic devices, such as Arduino, also advances a platform specifically designed for Internet of Things projects called the Arduino IoT Cloud. In this discussion, the author implements the usage of Arduino IoT Cloud by experimenting with a potentiometer to regulate the intensity or brightness of light on an LED through the Wi-Fi module NodeMCU based on ESP8266. The results of this implementation indicate that Arduino IoT Cloud can be operated to receive analog data from the potentiometer and exhibits stable performance in both receiving and reading data from it. These results are expected to serve as a reference for the development of Internet of Things technology by leveraging Arduino IoT Cloud and potentiometers